Migrant penalties in educational achievement : second-generation Immigrants in Western Europe - Borgna, Camilla (Changing welfare states., 2017)
The integration of second-generation immigrants has proved to be a major challenge for Europe in recent years. Though these people are born in their host nations, they often experience worse social and economic outcomes than other citizens. This volume focuses on one particular, important challenge: the less successful educational outcomes of second-generation migrants. Looking at data from seventeen European nations, Camilla Borgna shows that migrant penalties in educational achievement exist in each one - but that, unexpectedly, the penalties tend to be greater in countries in which socioeconomic inequalities in education are generally more modest, a finding that should prompt reconsideration of a number of policy approaches.